PENYESUAIAN ORGANISASI TEMPAT DUDUK TERHADAP KEBUTUHAN INDIVIDUAL DAN HASIL BELAJAR SISWA - Aah Siti Fatimah; Prihatini Prihatini (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2023)
This study aims to determine the adjustment of seats to individual needs and student learning outcomes, especially on research results. There are still schools where the teacher has not made seat adjustments. As for the formulation of the problem of this research is how the effect of adjusting the organizational structure of the seats on the individual needs of students and how the effect of adjusting the seating organization on student learning outcomes. In this study, researchers took one of the elementary schools in the city of Bandung. The sample used as a data source is 23 grade 5 students. Data collection was carried out by direct observation, interviews and documentation studies. The time for carrying out the research was October-November 2022 at one of the public elementary schools in the city of Bandung. Seating organization adjustments can help solve individual student needs, this is because seating arrangements are adjusted to learning methods so that students can analyze student learning needs. With seating arrangements the teacher can reach all students by grouping students according to their learning needs, and answering according to the formulation of the problem.